Alloy formation in nanostructured silicon - Gao, Bo; Sinha, Saion K.; Fleming, Les; Zhou, Otto (Advanced Materials, 2001)
250 citations (Crossref) [2023-10-31] Citation Key Alias: pop00001 tex.type: [object Object]
Keywords: dept.phy

Microstructure and physical properties of ferroelectric-gate memory capacitors with various buffer layers - Caragianis-Broadbridge, Christine; Han, J; Ma, T P; Lehman, Ann Hein; Zhu, Wenjuan; Luo, Zhijiong; Pechkis, Daniel; Laube, Bruce L (MRS Proceedings, 2001)
This paper reports the microstructure and physical properties of ferroelectric capacitors formed from SrBi2Ta2O9 (SBT) layers on Si with various buffer layers including jet-vapor deposited silicon nitride, zirconium oxide, hafnium oxide and thermally grown silicon oxide. Results from cross-sectional transmission electron microscopy (X-TEM), energy dispersive spectroscopy (EDS), X-Ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and non-contact atomic force microscopy (nc-AFM) data coupled with capacitance-voltage (C-V) and current-voltage (I-V) data indicate that both the microstructure and physical properties of SBT films deposited on silicon are dependent on the buffer layer material employed.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/010-822-098-712-167 tex.type: [object Object]
Keywords: Atomic force microscopy; Buffer layers; Capacitance; Capacitors; Electric currents; Electric potential; Energy dispersive spectroscopy; Ferroelectric devices; Ferroelectric-gate memory capacitors; Gates (transistor); Microstructure; Silica; Silicon nitride; Thin films; Transmission electron microscopy; X ray diffraction analysis; X ray photoelectron spectroscopy; dept.phy

Synthesis of silicon nano-dendrites - Sinha, Saion K; Gao, Bo; Zhou, Otto (MRS Proceedings, 2001)
A new branched silicon nanostructure called Silicon Nano-Dendrite (SiND) was prepared by Laser ablation. During the Laser ablation process, the Argon flow was switched on and off very fast and simultaneously decreasing the flow rate, to create a non-steady-state flow. The resulting structure will open up new avenues in molecular electronics as the FeSi2 nano-particle at the end can be used to grow nanotube-nanowire junctions.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-722-833-203-829 tex.type: [object Object]
Keywords: Carbon nanotubes; Electron diffraction; Fullerenes; Laser ablation; Molecular electronic applications; Nanostructured materials; Semiconducting silicon; Semiconductor quantum dots; Silicon nano-dendrites; Synthesis (chemical); Transmission electron microscopy; dept.phy